Impacto psicológico de la COVID-19 en una muestra de profesionales sanitarios españoles - Dosil Santamaría, María (Rev Psiquiatr Salud Ment, 2021)
INTRODUCTION: After the outbreak of the COVID-19 was considered a global pandemic in March 2020, the state of alarm was declared in Spain. In this situation, health professionals are experiencing high levels of stress due to the overload of work the pandemic is generating and the conditions in which they are working. The aim of this study was to evaluate the factors that can destabilize the mental health of these professionals in our context. MATERIALS AND METHODS: The sample was composed of 421 health professionals. The data were gathered by an online questionnaire sent to them by e-mail. The DASS-21 was used to assess anxiety, stress and depression, and the EAI to measure sleep difficulties. In addition, other descriptive variables that could be related to psychological symptomatology were collected from the sample. RESULTS: The results show that the COVID-19 pandemic has generated symptoms of stress, anxiety, depression and insomnia among health workers, with higher levels among women and older professionals. Some factors such as having been in contact with the virus or fear at work, triggered greater symptomatology. CONCLUSIONS: In this critical situation, professionals are in the front line and therefore, are directly exposed to certain risks and stressors. This contributes to the development of diverse psychological symptoms. Consequently, it is recommended to offer them psychological help in order to reduce the emotional impact of the COVID-19, and thus, to ensure not only the mental health of our health professionals, but also the adequate care they provide.